Real-world pattern-of-care analysis of primary cutaneous lymphomas radiation therapy among European organisation for research and treatment of cancer members - Elsayad, Khaled; Guenova, Emmanuella; Fournier, Beatrice; Fernandes, Carolina; Clementel, Enrico; Papadavid, Evangelia; Barry, Marie Beylot; Pavlotsky, Felix; Assaf, Chalid; Ortiz-Romero, Pablo L.; Kouloulias, Vassilis; de Masson, Adele; et al. (International journal of radiation oncology, biology, physics, 2025)
Purpose - We aim to determine the current treatment patterns and recommendations among physicians for cutaneous lymphomas and to identify the types of skin lymphomas for which existing radiation regimens need improvement. - Methods and Materials - A questionnaire from the European Organisation for Research and Treatment of Cancer was distributed to all members of the Cutaneous Lymphoma Tumour Group and Radiation Oncology Scientific Council. This online survey included 13 questions regarding treatment practices for patients with cutaneous lymphoma. The survey was conducted from August 21 to December 18, 2023. Frequency distributions and subgroup comparisons were calculated and analyzed. - Results - We collected 51 completed questionnaires from investigators from 19 countries specializing in cutaneous lymphoma treatment. Radiation doses varied significantly (range, 4-60 Gy). Based on the histologic entity, up to one-third of the investigators delivered hypofractionated regimens (range, 14%-35%). Reduced-dose radiation therapy (RT) was considered by 27% to 63% of investigators. Meanwhile, 18 (35%) investigators considered adapting the radiation dose to the response to immunochemotherapy when treating primary cutaneous diffuse large B cell lymphoma-leg type. Regarding total skin electron beam therapy, 91% of centers delivered reduced-dose regimens, and 18% of investigators applied ultrahypofractionated protocols. - Conclusions - RT in patients with cutaneous lymphoma is highly heterogeneous among the European Organisation for Research and Treatment of Cancer centers. The development of evidence-based recommendations for RT dose, fractionation, and technique for cutaneous lymphomas is required for optimization and standardization of treatment.
Online verfügbar: 14. November 2024, Artikelversion: 21. Februar 2025
Gesehen am 17.09.2025